2014
DOI: 10.1186/1472-6831-14-36
|View full text |Cite
|
Sign up to set email alerts
|

Taste hyposensitivity in Japanese schoolchildren

Abstract: BackgroundThere is some research on taste disorder/hyposensitivity in special groups such as the elderly or patients presenting with specific taste problems, however few studies have been conducted among young populations. The objectives of this study were to estimate the prevalence of taste hyposensitivity and to investigate the relationship between taste hyposensitivity and oral health status in Japanese schoolchildren.MethodsSubjects were 237 primary and 112 junior high school students in Saitama Prefecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The strong association between inflammation and taste impairment suggested that inflammation might affect the pathogenesis of taste dysfunction (37) . However, the difference was not statically significant, this agreed with Ohnuki et al, which found that taste hyposensitivity had little association with oral health status, such as dental plaque and gingival status (39).…”
Section: Discussionsupporting
confidence: 86%
“…The strong association between inflammation and taste impairment suggested that inflammation might affect the pathogenesis of taste dysfunction (37) . However, the difference was not statically significant, this agreed with Ohnuki et al, which found that taste hyposensitivity had little association with oral health status, such as dental plaque and gingival status (39).…”
Section: Discussionsupporting
confidence: 86%
“…Ohnuki et al 15 found that 6% of children had sweet hyposensitivity, 21% sour hyposensitivity, 6% bitter hyposensitivity, and 14% salty hyposensitivity; this group also used whole-mouth taste testing. In a study of 761 children and adults (approximately 75% were 20 years or older), the prevalence of hypogeusia was reported as approximately 5%.…”
Section: Discussionmentioning
confidence: 99%
“…Salt taste recognition thresholds are commonly conducted with a range of salt solutions and presented one at a time. Children simply reported whether they could identify the taste [ 74 , 75 , 76 , 77 ]. Children’s recognition thresholds of salty taste fall about 9 times above children’s salt detection threshold and vary from 0.17 to 0.18% ( w / v ) NaCl.…”
Section: Salt Taste Perception Of Childrenmentioning
confidence: 99%
“…Children’s recognition thresholds of salty taste fall about 9 times above children’s salt detection threshold and vary from 0.17 to 0.18% ( w / v ) NaCl. Two studies found higher thresholds, but technically speaking they did not measure thresholds because of the limited number of solutions which were offered [ 76 , 77 ]. In adults, salt recognition thresholds vary, as is the case with children.…”
Section: Salt Taste Perception Of Childrenmentioning
confidence: 99%